Oligosaccharide Ligands of Galectin-4 and Its Subunits: Multivalency Scores Highly - Slámová, Kristýna; Červený, Jakub; Mészáros, Zuzana; Friede, Tereza; Vrbata, David; Křen, Vladimír; Bojarová, Pavla (Molecules, 2023)
Galectins are carbohydrate-binding lectins that modulate the proliferation, apoptosis, adhesion, or migration of cells by cross-linking glycans on cell membranes or extracellular matrix components. Galectin-4 (Gal-4) is a tandem-repeat-type galectin expressed mainly in the epithelial cells of the gastrointestinal tract. It consists of an N- and a C-terminal carbohydrate-binding domain (CRD), each with distinct binding affinities, interconnected with a peptide linker. Compared to other more abundant galectins, the knowledge of the pathophysiology of Gal-4 is sparse. Its altered expression in tumor tissue is associated with, for example, colon, colorectal, and liver cancers, and it increases in tumor progression, and metastasis. There is also very limited information on the preferences of Gal-4 for its carbohydrate ligands, particularly with respect to Gal-4 subunits. Similarly, there is virtually no information on the interaction of Gal-4 with multivalent ligands. This work shows the expression and purification of Gal-4 and its subunits and presents a structure-affinity relationship study with a library of oligosaccharide ligands. Furthermore, the influence of multivalency is demonstrated in the interaction with a model lactosyl-decorated synthetic glycoconjugate. The present data may be used in biomedical research for the design of efficient ligands of Gal-4 with diagnostic or therapeutic potential.
Keywords: sacharidy; oligosacharidy; galektiny; galektin 4; nádory; Oligosaccharides; Ligands; Galectin 4; Humans; ligandy; lidé; Carbohydrates; Galectins; Neoplasms